THE REFERENCE QUALITY AND CONTEXTUALITY OF ISLAMIC EDUCATION MATERIALS FOR THE ELEMENTARY SCHOOL - Anwar Mujahidin; Ju'subaidi (Al-A'raf : Jurnal Pemikiran Islam dan Filsafat, 2020)
Studies on the development of teaching materials have been dominated by a pedagogical orientation to develop learning objectives, strategies, and evaluation. Not many studies have been carried out on the scientific structure of teaching materials. This study tries to examine the relationship between Islamic education teaching materials in the sub-chapter of Al-Qur'an based on the authoritative Qur'anic exegesis. Studying Islamic education teaching materials from the reference sources aims to ensure the quality of the teaching materials. By focusing the study on analyzing the materials about the stories and models of the prophet Adam and Ayub, through the critical discourse analysis method on how the sources are used, and how the context of the material is presented, the results of this study reveal that the materials teaching of Islamic education, about the story of prophet Adam and Ayub, do not refer to the books of Qur'anic exegesis. The explanation model is textual. Partial values are provided, such as the repentance of the prophet Adam and the patience of Ayub. Therefore, this study recommended that the development of Islamic education teaching materials in the chapter of the prophet stories refer to the authoritative Qur'anic interpretation books so that the materials are richer, better in quality, and actual.